The Hague Convention on Protection of Children and Co-operation in Respect of Inter-country Adoption Seeking the Cultural Relativism of the Inter-country Adoption - Šklebená, Karolína (2013)
This thesis focuses on the rights of the child in respect to the inter-country adoption. It aims to seek the notions of cultural relativism within those fundamental rights which are immediately applicable on the process of adoption. The thesis bases its theoretical framework on the current discourse on the universality of human rights. The theory of the three levels of cultural relativism is applied on the Hague Convention on Protection of Children and Co-operation in Respect of Inter-country Adoption to demonstrate the cultural relativism of the Convention itself.